Customized Hardware Crypto Engine for Wireless Sensor Networks - Medhat Awadalla; Ahmed Al Maashri; Lavanya Pathuri; Afaq Ahmad (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
Nowadays, managing for optimal security to wireless sensor networks (WSNs) has emerged as an active research area. The challenging topics in this active research involve various issues such as energy consumption, routing algorithms, selection of sensors location according to a given premise, robustness, and efficiency. Despite the open problems in WSNs, already a high number of applications available shows the activeness of emerging research in this area. Through this paper, authors propose an alternative routing algorithmic approach that accelerate the existing algorithms in sense to develop a power-efficient crypto system to provide the desired level of security on a smaller footprint, while maintaining real-time performance and mapping them to customized hardware. To achieve this goal, the algorithms have been first analyzed and then profiled to recognize their computational structure that is to be mapped into hardware accelerators in platform of reconfigurable computing devices. An intensive set of experiments have been conducted and the obtained results show that the performance of the proposed architecture based on algorithms implementation outperforms the software implementation running on contemporary CPU in terms of the power consumption and throughput.